The Relationship between the International Criminal Court and Africa: From Cooperation to Confrontation? - Birhanu, Alebachew Enyew (Bahir Dar University Journal of Law, 2022)
AbstractThe International Criminal Court (ICC) was set up by virtue of the Rome Statute to prosecute and punish core crimes â€“ genocide, crimes against humanity, war crimes, and crimes of aggression. The ICC has jurisdiction over such crimes in States Parties to the Rome Statute and other States whose situation is referred to it by the Security Council. To date, the ICC has opened 18 cases in 8 situations which are all from Africa. As a result, some African leaders complained that the ICC has unfairly targeted Africans and described the Court as â€œa Court of Western countries.â€ The African Union has also referred to the ICC as an impediment to peace and has eventually called African ICC member States for non-cooperation with the Court. This article thus explores the relationship between the ICC and Africa and examines some criticisms of the Court in the exercise of its jurisdiction in Africa.